HIPERREALITAS HERO PADA IKLAN TELEVISI PRODUK SABUN DALAM MEMBENTUK PERILAKU KONSUMSI ANAK (Tinjauan Mitologi Barthes Pada Iklan Lifebuoy Changing Colour Handwash) - Atiqa Khaneef Harahap (Universitas Bunda Mulia, 2015)
This study dismantle the hero hyperreality that is packaged in a product marketing practices targeting children. This study can explain about how advertising is reduced to explain consumption mark on contemporary society as expressed in the theory of consumer society. This study bases itself on competitive market conditions becomes its own pressure for manufacturers to update their strategy in marketing the products. This condition makes the manufacturers to shift in their marketing communications activities which originally ranged in to inform turn out to be the creator of the fake images through the use of myth to encourage consumption. Manufacturers urged by the need to secure the flow of production amid strong competition for market share. Producing needs through sign into how to resolve the problem of the production flow. According to Baudrillard consumption in contemporary society is not just using, wearing or digest but the consumption is absorbing the signs. Society is directed into a storefront sign and negate self-reflection. This research is critical to the design of qualitative methods Barthes semiotics. As a result, hyperreality hero performed by shifting the meaning of hero who is identified with possession of strength and fight while the product is positioned as an enabler to become ‘’jagoan’’ Keywords: Hero Hiperreality, Children, Advertising, Consumer Society